The nature and content of the interior design licensure exam and its implications on the enhancement and safeguard of life, health, and property - Lopez, Paolo Francis D.; Quevedo, Ma. Teresa P. (Quezon City UP College of Home Economics, 2012)
The study aimed to determine the nature and content of the interior design licensure exam in the Philippines and to verify if the exam is aligned with the competencies required in practice, with the end goal of enhancing and safeguarding life, health, and property. The study made use of a quantitative approach and utilized survey as research method. Purposive sampling and snowball sampling were utilized to select the 30 respondents of the survey composed of interior designers who took the interior design licensure exam from 2007 to 2011. The instrument of the study was a survey questionnaire sent through email and an online social media website. Results showed that the two most common types of test in the licensure exam were multiple-choice and design presentation. In general, the licensure exam was able to test the examinees on the knowledge and competencies required in practice. The top 5 knowledge and competencies which were tested in the licensure exam are: (1) ethical business practices that are aligned with the Code of Ethics provided by the Board of Interior Design, (2) preparation of shop drawings (full-sizing, technical drawings etc.) in furniture construction that consider anthropometrics and ergonomics, (3) various statutes and codes that regulate the practice of interior design (R.A. 8534 - Interior Design Law), (4) knowledge in basic furniture construction and furniture materials, (5) and design conceptualization based on the principles and theories of interior design. Data analysis revealed however that there was no significant evidence to determine the alignment of the licensure exam as a whole to the enhancement and safeguard of life, health, and property as prescribed in RA 8534.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Interior decoration -- Philippines -- Examinations, questions,etc